Impact Of Poetic Style For Pronunciation: A Systematic Literature Review - Wahyu Ariningsih, Tri (Pusat Publikasi Nusantara, 2023)
Linguistics' field of pronunciation studies how words are pronounced and their intended meanings, arrangement, and classification of sounds as linguistic components. Then pronunciation is often associated in the pronunciation of a poem. It started with an oral tradition because previously poetry was made to be performed. Focusing on the phonemic inventory of poetry, several studies have found a non-arbitrary relationship between the frequency of occurrence of certain phoneme classes and the